(untitled) (Eurasian Journal of Engineering and Technology, 2026)
Using methods of analytical analysis and scientific reasoning, the article highlights the role of land allocation and reallocation processes in the development of regional economic sectors, as well as presents scientific and practical recommendations for regulating and effectively managing these processes.